Flora of bryophytes from squares of the urban area of the city of Abaetetuba, Pará State, Brazil (Research, Society and Development, 2022)
Most Brazilian squares are composed of medium and large trees, but also other plants that go unnoticed due to their small size, such as bryophytes. This group of plants has great bioindicator potential, as many species are sensitive to environmental disturbances. Studies on bryophytes in urban squares are carried out sparsely in Brazil. Thus, the objective of this work was to inventory the bryophytes in two squares in the urban area of ​​Abaetetuba, state of Pará, Brazil, as well as to present an identification key for the recorded taxa and illustrations of some species. In the study area, fifteen species distributed in 12 genera and eight families were recorded, of which eight species belong to the Marchantiophyta division and seven to the Bryophyta division. The most representative families were Lejeuneaceae, with seven species, and Calymperaceae, with two species. The genera with highest species richness were Lejeunea Lib. (Lejeuneaceae), with three species, and Microlejeunea (Spruce.) Steph. (Lejeuneaceae), with two species. As for the substrate, 11 corticolous species and three chasmophytes species were collected. Thus, it is assumed that these data on the flora of bryophytes in urban areas demonstrate the importance of green areas, as refuges for several species, and it is expected that the results obtained in this study support further work on the flora of bryophytes in the region.